Trash and Threat: Assessing Knowledge, Attitude, and Practice on Solid Waste Management among Rural Communities in Longhouse Sibu, Sarawak - Lim, Siong Hee; Sam Froze, Jiee; Dayang Suhana, Abang Madzhi (RSIS International, 2026)
Objective: To assess knowledge, attitudes, and practices (KAP) related to solid waste management (SWM) among rural longhouse communities in Sibu, Sarawak, and to examine factors influencing behavioural outcomes. Methods: A cross-sectional community-based study was conducted among 51 residents using universal sampling. Data were collected באמצעות a trilingual interviewer-administered questionnaire adapted from Eshete et al. (2023). Descriptive and inferential analyses (t-tests and Pearson correlations) were performed using SPSS Version 27.0, with significance set at p < 0.05. Results: Respondents demonstrated moderate knowledge, positive attitudes, and suboptimal practices. Knowledge was positively correlated with attitude (r = 0.424, p = 0.002) and practice (r = 0.371, p = 0.007). Age showed a significant negative association with all KAP domains. Despite high awareness, sustainable practices such as recycling (31.4%) and waste segregation (37.3%) remained low. Conclusion: The findings highlight a significant knowledge–practice gap driven by structural and contextual constraints. Interventions should prioritise community-based education, decentralised waste systems, and policy implementation tailored to rural settings.